Are Securitizations in Substance Sales or Secured Borrowings? Capital‐Market Evidence* - Niu, Flora F.; Richardson, Gordon D. (Contemporary Accounting Research, 2006)
Abstract Two standard‐setting approaches have emerged globally to guide the choice of accounting for securitizations: the control and components approach ( SFAS No. 125 and SFAS No. 140 ) and the risks and rewards transfer approach ( IAS No. 39 ). A lack of consensus about derecognition accounting is a major impediment to achieving convergence in global standards that must be resolved. Thus, both SFAS No. 140 and IAS No. 39 will be reexamined, and evidence pertinent to the debate is timely and important. In this study, we present evidence consistent with the view of credit‐rating analysts, who view many securitizations as, in substance, secured borrowings. Specifically, for a sample of originators applying sale accounting guidance in SFAS No. 125 / 140 during the period 1997‐2003, we show that off‐balance‐sheet debt related to securitizations has, on average, the same risk‐relevance for explaining market measures of risk (that is, CAPM beta) as on‐balance‐sheet debt. We also find that, in a returns and earnings association framework, the pricing multiple on securitization gains declines as the amount of off‐balance‐sheet debt increases, implying that investors take off‐balance‐sheet debt into account when assessing the valuation‐relevance of such gains. For those who advocate the control and components approach to securitization accounting, our results suggest that, at least for frequent securitizers, the put option arising from implicit recourse is a “missing piece” that is not currently accounted for when calculating securitization gains. Our results challenge the extant measurement standards in SFAS No. 140 .